2018
DOI: 10.1039/c8nr01971a
|View full text |Cite
|
Sign up to set email alerts
|

Ozone-mediated synthesis of ceria nanoparticles

Abstract: We report a rapid, room temperature methodology to synthesize fluorite-structured ceria nanoparticles using cerium(iii) salts and ozone in the presence of short chain primary, secondary, and tertiary alcohols. This simple technique produced nanoparticles with higher oxygen vacancy compared to that of bulk ceria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Sub-3-nm crystalline ceria NPs were prepared by using an ozonemediated synthesis method reported by our group. [18,24] Briefly, to synthesize the ceria NPs, 0.5 g of Ce(NO 3 ) 3 • 6H 2 O (1.1 mmol) was dissolved in 20 mL of 200-proof ethanol. Ozone (0.5 g/hour) was bubbled through the ethanol-salt solution for 30 minutes, resulting in a reddish color of the reaction mixture.…”
Section: Synthesis and Characterization Of Ceria Npsmentioning
confidence: 99%
“…Sub-3-nm crystalline ceria NPs were prepared by using an ozonemediated synthesis method reported by our group. [18,24] Briefly, to synthesize the ceria NPs, 0.5 g of Ce(NO 3 ) 3 • 6H 2 O (1.1 mmol) was dissolved in 20 mL of 200-proof ethanol. Ozone (0.5 g/hour) was bubbled through the ethanol-salt solution for 30 minutes, resulting in a reddish color of the reaction mixture.…”
Section: Synthesis and Characterization Of Ceria Npsmentioning
confidence: 99%
“…The side product observed at 13.3 min was largely visible as a consequence of the excellent limits of detection (down to 4 ppm for organic carbonates) made possible by the ion-moderated partition high performance liquid chromatography (HPLC) method utilized for the sample analysis [26]. Furthermore, this HPLC method allowed for low (55°C column) temperatures for the analysis and thus allowed us a better opportunity to observe volatile or fragile side products than when the samples were analyzed by GC-MS. As shown in Fig.…”
Section: Effect Of Temperature On the Reaction Profilementioning
confidence: 99%
“…This postulation of surface modication effect was corroborated by a similar discussion by Slostowski et al for their syntheses of ceria nanocrystals in supercritical aliphatic alcohols. 18 The reaction yields of ceria NPs made with lithium acetates were found to be up to 8 times higher than those of our standard ozone-mediated method reported by Bhalkikar et al 14 Our TGA-IR analysis revealed that the as-synthesized samples also contained water and residual organics. As the NP samples were heated to 600 C, their weights decreased by about 20% with the evolution of water vapor, carbon dioxide, and organic vapor (Fig.…”
Section: Resultsmentioning
confidence: 49%
“…The additions of lithium acetate were found to greatly improve the reaction yields of our previously reported ozone-mediated synthetic method. 14 Briey, a reactant solution was rst prepared by dissolving cerium nitrate hexahydrate Ce(NO 3 ) 3 $6H 2 O (99.99% REO, Alfa Aesar, Tewksbury, MA) in ethanol with lithium acetate dihydrate. (LiOAc$2H 2 O 98%, Sigma-Aldrich, Milwaukee, WI) of various mole ratios with respect to Ce(NO 3 ) 3 $6H 2 O (hereaer referred as reactants ratio (LiOAc : Ce(NO 3 ) 3 ) ¼ 0 : 1, 1 : 1, 2 : 1, 3 : 1, 4 : 1, and 5 : 1).…”
Section: General Procedures For the Syntheses Of Ceria Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation